Implants of polyanionic collagen matrix in bone defects of ovariectomized rats - Cunha, Marcelo Rodrigues; Santos, Arnaldo Rodrigues [UNESP]; Goissis, Gilberto; Genari, Selma C. (Springer, 2008)
In recent years, there has been a great interest in the development of biomaterials that could be used in the repair of bone defects. Collagen matrix (CM) has the advantage that it can be modified chemically to improve its mechanical properties. The aim of the present study was to evaluate the effect of three-dimensional membranes of native or anionic (submitted to alkaline treatment for 48 or 96 h) collagen matrix on the consolidation of osteoporosis bone fractures resulting from the gonadal hormone alterations caused by ovariectomy in rats subjected to hormone replacement therapy. The animals received the implants 4 months after ovariectomy and were sacrificed 8 weeks after implantation of the membranes into 4-mm wide bone defects created in the distal third of the femur with a surgical bur. Macroscopic analysis revealed the absence of pathological alterations in the implanted areas, suggesting that the material was biocompatible. Microscopic analysis showed a lower amount of bone ingrowth in the areas receiving the native membrane compared to the bone defects filled with the anionic membranes. In ovariectomized animals receiving anionic membranes, a delay in bone regeneration was observed mainly in animals not subjected to hormone replacement therapy. We conclude that anionic membranes treated with alkaline solution for 48 and 96 h presented better results in terms of bone ingrowth.